Meta-Analysis of Interactions between Arbuscular Mycorrhizal Fungi and Biotic Stressors of Plants. (10th December 2013) - Yang, Haishui; Dai, Yajun; Wang, Xiaohua; Zhang, Qian; Zhu, Liqun; Bian, Xinmin
Abstract : Naturally, simultaneous interactions occurred among plants, herbivores, and soil biota, that is, arbuscular mycorrhizal fungi (AMF), nematodes, and fungal pathogens. These multiple interactions play fundamental roles in driving process, structure, and functioning of ecosystems. In this study, we conducted a meta-analysis with 144 papers to investigate the interactions between AMF and plant biotic stressors and their effects on plant growth performance. We found that AMF enhanced plant tolerance to herbivores, nematodes, and fungal pathogens. We also found reciprocal inhibition between AMF and nematodes as well as fungal pathogens, but unidirectional inhibition for AMF on herbivores. Negative effects of AMF on biotic stressors of plants depended on herbivore feeding sites and actioning modes of fungal pathogens. More performance was reduced in root-feeding than in shoot-feeding herbivores and in rotting- than in wilt-fungal pathogens. However, no difference was found for AMF negative effects between migratory and sedentary nematodes. In return, nematodes and fungal pathogens generated more reduction of root colonization in Non-Glomeraceae than in Glomeraceae. Our results suggested that AMF positive effects on plants might be indirectly mediated by competitive inhibition with biotic stressors of plants. These positive and negative interactions make potential contributions to maintaining ecosystem stability and functioning.